Chaplaincy service in the Army of Republic of Macedonia – Requirement, Importance and Justification - Goran Vasilevski (Bezbednosni Dijalozi, 2017)
Along with self-knowledge, human beings developed awareness of safety and the phenomena that are surrounding them. The awareness of security based on the efforts to survive resulted in adapting to various tools and their use for individual and collective protection and there are the beginnings of the need for arming and organizing military formations that are part of the base of human civilization. Phenomena that are surrounding, including birth, life, and death, contributed to developing awareness that there may be a supernatural or divine force that manages them. Therefore the basic human right to freedom of thought, expression, and religion is complementary with the right to freedom and security. Right here, as in the long history of warfares ‘in the name of God’ lays the relationship between military and religion, regardless of which confession it is. This interdependence of the army with religion can also be considered absurd and inclusive. Absurd, because the base of every religion is encouraging love and understanding, and the armies and their weapons are used for killing and destruction. It is Inclusive because religious members of the armed forces have the need for spiritual justification of the call they chose as professional determination. The biggest challenge of this paper is the observation of the decisions on this issue in countries that have a long tradition of involvement of clergy within the armed forces, the armies of countries transiting from one ideological system to another, as well as possible solutions for introducing clerical service in countries whose armed forces are made up of members of several confessions. In this context will be considered the need and justification for introducing chaplaincy service in the Army of the Republic of Macedonia.